2000
DOI: 10.1086/317134
|View full text |Cite
|
Sign up to set email alerts
|

GRB 991216 Joins the Jet Set: Discovery and Monitoring of Its Optical Afterglow

Abstract: The optical light curve of the energetic c-ray burst GRB 991216 is consistent with jetlike behavior in which a power-law decay steepens from t~1.22B0.04 at early times to t~1.53B0.05 in a gradual transition at around 2 days. The derivation of the late-time decay slope takes into account the constant contribution of a host or intervening galaxy, which was measured 110 days after the event at R \ 24.56^0.14, although the light curve deviates from a single power law whether or not a constant term is included. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
2
2

Year Published

2001
2001
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 29 publications
8
112
2
2
Order By: Relevance
“…3), tends to fall near the isotropic models and along a 1 a 2 the jet models. Well-observed bursts with light-curve breaks are shown : GRB 990123 (Holland et al 2000), GRB 990510 (Stanek et al 1999), GRB 991216 (Garnavich et al 2000a ;Halpern et al 2000), GRB 000301C (Garnavich, Loeb, & Stanek 2000b ;Rhoads & Fruchter 2001), GRB 980519 (Jaunsen et al 2001), GRB 000926 (Price et al 2001a). We do not include GRB 991208 (Castro-Tirado et al 2001), which is well observed until the "" break ÏÏ deÐned by only one point.…”
Section: Discussionmentioning
confidence: 94%
“…3), tends to fall near the isotropic models and along a 1 a 2 the jet models. Well-observed bursts with light-curve breaks are shown : GRB 990123 (Holland et al 2000), GRB 990510 (Stanek et al 1999), GRB 991216 (Garnavich et al 2000a ;Halpern et al 2000), GRB 000301C (Garnavich, Loeb, & Stanek 2000b ;Rhoads & Fruchter 2001), GRB 980519 (Jaunsen et al 2001), GRB 000926 (Price et al 2001a). We do not include GRB 991208 (Castro-Tirado et al 2001), which is well observed until the "" break ÏÏ deÐned by only one point.…”
Section: Discussionmentioning
confidence: 94%
“…The optical AG of GRB 000301c is practically unextinct, that of GRB 000926 has strong extinction in the host galaxy (e.g., Fynbo et al 2001) and that of GRB 991216 has strong extinction both in the host galaxy and in ours (e.g., Halpern et al 2000). We discuss GRBs 991208, 000418, 000510, 990123 and 970508 in slightly less detail.…”
Section: Thus the Total Number Of Parameters In Our Broadband Fits Imentioning
confidence: 97%
“…The NIR/optical data for this GRB are from Halpern et al (2000) and Garnavich et al (2000a); the radio data from Frail et al (2000b). In Fig.…”
Section: Grb 991216mentioning
confidence: 99%
“…Left: PCA determination of index for GRB 000115. Right: ASM/PCA/Chandra decay of GRB 991216, reported in Halpern et al [8] four derived from Locburst and one from the ASM; Table 1. In each case celestial positions were promptly reported to the community.…”
Section: Observations Of Afterglows With the Pcamentioning
confidence: 99%
“…• Optical afterglow in GRB 991216 with a break in the decay curve indicating a jet in interstellar medium [8], radio emission [4], and a reported lower-limit to the redshift, z > 1.02 [20].…”
Section: Observations Of Afterglows With the Pcamentioning
confidence: 99%